Effect analysis of generator governor system and its frequency mode on inter-area oscillations in power systems. (March 2018) - Liu, Ziquan; Yao, Wei; Wen, Jinyu; Cheng, Shijie
Highlights: Mechanism of an ultra-low frequency oscillation caused by governor system is investigated. Influence of the frequency mode on inter-area oscillation is analyzed. The influence of governor dead band should be taken into consideration. Simulation results in a practical interconnected system verify the correctness of the analysis. Abstract: The governor system of a synchronous generator not only can influence the damping characteristics of inter-area oscillations but also introduces a special ultra-low frequency mode into the power system. This mode, called frequency mode, has a lower frequency than that of inter-area modes and would appear when the governor system regulates the rotor speed. In this paper, the influence of governor system on the damping characteristics of inter-area oscillations is investigated by using the torque analysis theory. Then the feature of the frequency mode and its influence on inter-area oscillations are analyzed by using a 4-machine 2-area benchmark system. The analysis results show that the frequency mode is a control mode of the governor system and its damping ratio is mainly influenced by the parameters of the proportional-integral-derivative (PID) controller used for the governor system. When the governor system makes the damping ratio of an inter-area mode negative and the dead band is taken into account, the inter-area oscillation will gradually become an equal amplitude oscillation in case the damping of the frequency mode is relatively strong, while the inter-area oscillation will appear like a beat frequency oscillation in case the damping of the frequency mode is relatively weak. Finally, simulation results of a practical large-scale interconnected power system validate the effectiveness of the above analysis results.